Non-Vital Bleaching for a Single Dark Anterior Tooth: A Case Report - Aldaiji, Daij (British Journal of Healthcare and Medical Research, 2024)
Restorative dentistry is a mixture of art and science, dental bleaching is a conservative, less expensive option to restore the color of endodontically treated discolored teeth. Purpose: the aim of this study is to report a case of a non-vital endodontically treated single dark anterior tooth by using a combination of bleaching techniques. Case: 35 years old man complained about a single dark upper anterior tooth which was Re-endodontically treated 4 months ago. case management: A combination of closed internal and external bleaching treatment was taken, and the result was satisfactory for the patient. Conclusion: bleaching using a combination of closed internal& external methods for a single dark tooth that has received an endodontics treatment shown to be effective. Safe and return teeth to their desired color.